REDESAIN STRUKTUR BAWAH BANGUNAN GEDUNG: STUDI KASUS PERENCANAAN PONDASI TAPAK GEDUNG SEKOLAH DASAR NEGERI (SDN) 12 MUNTEI, MENTAWAI - Winda Fitria; Merley Misriani; Fielda Roza (LPPM Universitas Abdurrab, 2024)
Mentawai islands are one of the regions that utilize the tourism sector to support their development. Mentawai is a favorite destination for surfing tourists from abroad. In general, tourism in Mentawai island has a good impact on the local economy. Infrastructure development in the Mentawai island is still lagging behind compared to other cities in West Sumatera. The development process in Mentawai should receive serious attention considering that Mentawai is an prone area to earthquake and tsunami disasters. The increase in the potential for earthquake and tsunamis is not matched by the communit’s readiness to face them. To reduce the risk of loss live in earthquake prone area, earthquake resistant building standards are very important to implement. Earthquake resistant buildings must be applied from the planning stage, not just during the construction process. SDN 12 Muntei is one of the buildings that can be used by the public as an elementary school. Investigation of the initial design of the building foundation in previous research found that the allowable capacity of the foundation not be able to support axial load on the building, so a redesign of the foundation cross section was recommended. After redesigning the foundation with a fixed footing type as in previous research, it is recommended that the foundation be at a depth of (D) = 1.5 meter with a width of (B) = 1.3 meter. The Safety Factor (SF) value to determine the allowable capacity of the foundation (Qa) is taken as 3. From the results the analysis of the allowable capacity with new cross section dimension, the value of Qa= 378.76 KN and the value of the maximum load on building (Pmaks)= 339 KN. The results of this analysis show that the crosssection requirements and can be used.